Puisi media penanaman nilai-nilai karakter: suatu kajian ekologi sastra - Muliadi, Muliadi; Firman, Firman; Rabiah, Sitti (Universitas Mulawarman, 2024)
Ecological literature is an approach or method used to understand the relationship between ecology and literature. Literature connects human life with the surrounding natural environment. The focus of the study is how literature parses its environment so that it can be a concern for its readers that the natural environment is an ecosystem for human life so that it needs to be maintained and or preserved. The poems that are the object of study in this research are poems that have ecological literary nuances. The ecological literature referred to in this study is poetry that talks about the sea. The sea as a vast source of livelihood, so the poet is interested in writing in his work so that readers understand about the sea as one of the ecosystems that is very urgent in the life of mankind in the universe or on this planet earth. To reveal the character values of the selected poems, an ecological approach to literature is used.